Formation of Periodical Authorship in 1920s Korea Distant and Close Reading (Taylor & Francis, 2023)
Korean Literature, Periodical Authorship, Twentieth Century Literature
English
Keywords: Korean Literature, Periodical Authorship, Twentieth Century Literature; thema EDItEUR::D Biography, Literature and Literary studies::D Biography, Literature and Literary studies::DS Literature: history and criticism